Equações diferenciais ordinárias na formação inicial de professores de Matemática através da resolução de problemas - Melo, Igor Raphael Silva de (2021)
This paper analyzes the methodological strategies of Problem Solving in Ordinary Differential Equations, highlighting its importance nowadays and the need for teaching to make meaningful learning in initial and continuing education of mathematics teachers. This is a bibliographic study and qualitative intervention in the context of the scientific methodology of Romberg-Onuchic (2014). We offered an extension course called "ODE through Problem Solving: from practice to theory", intended for the students the of Mathematics Teaching Course from the Universidade Federal de Campina Grande (UFCG), Cuité campus, to teaching course students from other universities and teachers from different states of Brazil. The course was taught virtually and we used the Zoom Meetings applications with simultaneous rooms for the dynamics of the virtual meetings and WhatsApp for instantaneous contacts and task records. The collection and analysis of the data collected in this research occurred through the application of questionnaires, audio and video recordings of the remote meetings, production material of the participants, chatting circle, and notes made in the field journal. The descriptions and analysis of the meetings and the evaluation questionnaire reveal the changes in the participants' attitude towards the construction and reconstruction of concepts, theorems, and applications of ODE and their implications in the formative process of understanding the mathematical concepts addressed, as well as the relevance of experiencing a new approach to work on this theme through Problem Solving. The results indicate that this paper contributed with teachers and future teachers of mathematics, favoring learning, in order that they can develop a reflective practice when working in the perspective of Problem Solving, creating a new path regarding the initial and continuing education of teachers. It is concluded, then, that our work created a link between the Methodology of Teaching-Learning-Assessment of Mathematics through Problem Solving, the initial and continuing education of teachers and Ordinary Differential Equations, besides the possibilities in the context of remote teaching.